2020
DOI: 10.32535/ijabim.v5i2.855
|View full text |Cite
|
Sign up to set email alerts
|

Tax Payment Revenue Ratio as Tax Risk Analysis for Manufacture Industry in Indonesia after Tax Amnesty Policy

Abstract: Indonesia's Tax Amnesty potentially will increase state tax revenues in rupiah; however, it cannot increase tax compliance as measured by the tax ratio value. Tax audit as a law enforcement needs to be carried out on taxpayers with high risk in utilizing tax amnesty policies for tax avoidance. By comparing the ratio of tax payment revenue (TPR) in manufacturing companies listed on IDX, this study finds that most of the samples are indicated to have a high risk of tax avoidance, since the value of TPR is signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…By referring to the principles of tax collection introduced by Adam Smith, the tax administration in Indonesia carries out a tax audit process to ensure that the taxpayer has reported and paid income tax according to applicable regulations. Tax audits are also carried out on companies with high risk (Santoso & Erlina, 2020). According to the tax theory, a tax audit is the only tool to prevent tax evasion (Kuchumova (Paramonova), 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…By referring to the principles of tax collection introduced by Adam Smith, the tax administration in Indonesia carries out a tax audit process to ensure that the taxpayer has reported and paid income tax according to applicable regulations. Tax audits are also carried out on companies with high risk (Santoso & Erlina, 2020). According to the tax theory, a tax audit is the only tool to prevent tax evasion (Kuchumova (Paramonova), 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that the relationship between firm value and firm financial performance was not moderated by dividend policy to shareholders. Kraaijenbrink in Santoso (2020) explains that to be able to create high corporate value by carrying out company management decisions well. This is in accordance with the stakeholder theory which explains that the company must be able to equalize and unite the various interests of all stakeholders or stakeholders involved in the company.…”
Section: Introductionmentioning
confidence: 99%
“…Taxes are a citizen's duty to pay the state without directly compensation (Sepriana, 2021). Since the Indonesian government accounts for more than 80% of revenue from taxes, this becomes the importance of taxes for income (Santoso, M. R., & Erlina, 2020). Entertainment tax is one type of local tax that has a significant contribution in terms of increasing regional income, because in Indonesia, especially Deli Serdang Regency, so many entertainment venues are developing so fast.…”
Section: Introductionmentioning
confidence: 99%